2018
DOI: 10.1039/c7cp08472b
|View full text |Cite
|
Sign up to set email alerts
|

Control of triplet state generation in heavy atom-free BODIPY–anthracene dyads by media polarity and structural factors

Abstract: A family of heavy atom-free BODIPY-anthracene dyads (BADs) exhibiting triplet excited state formation from charge-transfer states is reported. Four types of BODIPY scaffolds, different in the alkyl substitution pattern, and four anthracene derivatives have been used to access BADs. Fluorescence and intersystem crossing (ISC) in these dyads depend on donor-acceptor couplings and can be accurately controlled by substitution or media polarity. Under conditions that do not allow charge transfer (CT), the dyads exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 87 publications
8
93
1
Order By: Relevance
“…The same researchers prepared a series of analog Bodipy-derived electron donor/acceptor dyads. The dyads generally showed satisfactory SOCT-ISC (Filatov et al, 2018). Zhang also prepared Bodipy-based electron donor/acceptor dyads, and the SOCT-ISC was observed (Zhang and Feng, 2017;Hu et al, 2019).…”
Section: Charge Recombination-induced Isc In Bodipy Derivativesmentioning
confidence: 88%
“…The same researchers prepared a series of analog Bodipy-derived electron donor/acceptor dyads. The dyads generally showed satisfactory SOCT-ISC (Filatov et al, 2018). Zhang also prepared Bodipy-based electron donor/acceptor dyads, and the SOCT-ISC was observed (Zhang and Feng, 2017;Hu et al, 2019).…”
Section: Charge Recombination-induced Isc In Bodipy Derivativesmentioning
confidence: 88%
“…[21] The 1,7methyl groups on the boron dipyrromethene (Bodipy) moiety play as imilar role in Bodipy-derived electron donor/acceptor dyads showingS OCT-ISC. [22][23][24][25][26] We found that the presence of peri-H(C) of electron donor phenothiazine is helpful for conformation restriction. [24,27,28] However,i na ll these molecular structural motifs, rotation about the CÀCo rt he CÀNl inker is not fully restricted, and various conformationsa re still accessible with thermale nergy.D eviation from the orthogonal geometry may be detrimental to the SOCT-ISC efficiency.T hus, fully rigid linkers are desired for linking the electron donora nd acceptor in these dyads, but this kind of linker is difficult to obtain from the point of view of synthesis.…”
Section: Introductionmentioning
confidence: 92%
“…Phenylene-separated BODIPY-anthracene and pyrene dyads 54 and 55 were reported to undergo PET in polar solvents, however both exhibit very low singlet oxygen quantum yields ( ≈ 0.01), evidencing low efficiency of the triplet state formation. 59,64 The dihedral angle between the subunits in 54 is approximately 53°, suggesting that SOCT-ISC is not operative in this system. Majima and co-workers described structurally similar BODIPYanthracene dyads 56a-b, which do not exhibit PET in dimethyl sulfoxide and methanol.…”
Section: Directly Linked Dyads Vs Spacer-separated Bodipy Dyadsmentioning
confidence: 99%